Environmental, Social, and Governance Impact on Energy Sector Default Risk—Long-Term Issuer Credit Ratings Perspective - Chodnicka-Jaworska, Patrycja (Frontiers in Energy Research, 2022)
The aim this study is to analyze the impact of environmental, social, and governance (ESG) measures on energy sector credit ratings. The main hypothesis is as follows: The ESG measures have had a significant impact on energy sector credit ratings during the COVID-19 crisis. The analysis has been conducted by using long-term issuer credit ratings presented by the main credit rating agencies. To verify the hypothesis, quarterly data from financial statements, macroeconomic data, and ESG measures for all companies listed on the stock exchanges from all over the world for the 2000–2021 period were collected. The sector was divided into sub-samples according to the type of sector and the moment of the COVID-19 crisis. It was noticed that a stronger reaction of credit ratings during the COVID-19 crisis on ESG factors, than that before it, was also observed, and confirms the increasing role of ESG measures in the financial market. On the other hand, credit rating agencies take into consideration ESG factors during the first estimation. Later, the mentioned variables lose their importance. This is based on a few reasons. It is still a small sample of entities that publish non-financial statements connected with ESG. Some countries have yet to implement regulations associated with climate risk. The significance of electricity power consumption and CO2 emissions confirms the significance of the mentioned direct or indirect impact of ESG factors. Credit rating agencies are not willing to change credit ratings because usually companies from the energy sector, especially from coal and oil and gas subsectors, are large entities. They sometimes receive financial support from governments. Governments are also stakeholders that create a lower risk of default. In less developed countries, coal is one of the main energy sources, and costs connected with alternative, renewable energy are more expensive. The prepared research also suggests that particular ESG measures have varying significance on credit ratings. Therefore, it can help to analyze and build models by investors. It will not be without significance for estimating the default risk and the cost of the capital. In most cases, the most significant measure is the E factor.